2009
DOI: 10.1111/j.1476-5381.2009.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the JNK signalling pathway enhances proteasome inhibitor‐induced apoptosis of kidney cancer cells by suppression of BAG3 expression

Abstract: Background and purpose: Proteasome inhibitors represent a novel class of anti-tumour agents that have clinical efficacy against haematological and solid cancers. The anti-apoptotic protein BAG3 is a member of the Bcl-2-associated athanogene family. We have previously shown that BAG3 is up-regulated after exposure to proteasome inhibitors and that inhibition of BAG3 sensitized cells to apoptosis induced by proteasome inhibition. However, the mechanisms by which proteasome inhibition induced BAG3 expression rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Furthermore, both JNK and p38 MAPK have been linked to the pathogenesis and progression of HCC. 30,31 Treatment with CLX inhibited phosphorylation of p38 MAPK and JNK1/2 in both cell lines, whereas treatment with MG, in agreement with other reports, 32,33 promoted phosphorylation of p38 MAPK and JNK1/2 in a dose-dependent manner in both cell lines (Fig. 4).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, both JNK and p38 MAPK have been linked to the pathogenesis and progression of HCC. 30,31 Treatment with CLX inhibited phosphorylation of p38 MAPK and JNK1/2 in both cell lines, whereas treatment with MG, in agreement with other reports, 32,33 promoted phosphorylation of p38 MAPK and JNK1/2 in a dose-dependent manner in both cell lines (Fig. 4).…”
supporting
confidence: 91%
“…However, activation of these stress sensitive protein kinases did not appear to be involved in combination-induced cell death in HCC cells, but rather, as reported by others, their activation seem to be associated with a protective response against the drug treatment. 33 At the molecular level, proteasome inhibitors and celecoxib exert antitumor activity via different mechanisms, however both are known to trigger endoplasmic reticulum stress response (ESR), which kills cancer cells. [9][10][11][12][18][19][20] The important role of ESR in tumor cell growth and survival has been recently recognized.…”
Section: Discussionmentioning
confidence: 99%
“…21,[53][54][55][56] In addition, we have reported that MAPK8/9 is involved in BAG3 induction mediated by proteasome inhibitors. 57 MAPK8/9/10 inhibitor SP600125 demonstrated a dosedependent reduction of LC3-II production elicited by MG132 (Fig. 5A).…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies have demonstrated that JNK is activated in the heart during reperfusion following ischemia but not by ischemia alone (30). Furthermore, studies in nonmyocytes suggest that activation of JNK enhanced BAG3 gene expression, whereas JNK inhibitors decreased BAG3 expression (31,32). Therefore, there may be a feedback loop that decreases JNK activation in the heart when BAG3 levels are high and increases JNK activation when BAG3 levels are low.…”
Section: Discussionmentioning
confidence: 99%